CADCAM Arch Bars: A Technical Note. (21st September 2021) - Tache, Ana; Huys, Stijn E. F.; Mommaerts, Maurice Y.
Study Design: Technical note. Objective: Computer-aided design and computer-aided manufacturing (CADCAM) is commonly used in craniomaxillofacial (CMF) surgery because of its advantage in customizing medical devices. We used this technology to create individualized, resin-bonded 3-dimensionally printed titanium arch bars. Method: This article describes a patient specific, three-dimensionally (3D) printed, resin-bonded arch bar as an alternative to the classical intermaxillary fixation systems. Results: The ease of application and removal, as well as the protection of the periodontal and cheek tissues, and operator fingers, made this a comfortable technique for both the patient and practitioner. Conclusions: A patient-specific 3D-printed titanium arch bar can be useful in the arsenal of the maxillofacial surgeon.